A transesophageal echocardiography study: traumatic left atrial appendage and left upper pulmonary vein dissection. - Leeson, P; Dass, S; Mitchell, A; Ryding, A; Becher, H (2007)
Transesophageal echocardiography was requested for a 20-year-old woman admitted to the intensive care department after being involved, as a restrained driver, in a road traffic accident. During the study a striking abnormality was noted around the left atrial appendage and left upper pulmonary vein. The clinical history of blunt chest trauma, and echocardiographic appearances suggestive of a flap, indicated the diagnosis was left atrial appendage and left upper pulmonary vein dissection. The report summarizes the literature on traumatic injury to the left upper pulmonary vein and left atrial appendage and demonstrates the importance of comprehensive echocardiographic studies to identify unexpected pathology.